Digital Tessellation for Geometry Learning in Primary School: A Quasi-Experimental Study - Scippo, Stefano; Madiai, Serena; Cuomo, Stefano (Journal of information technology education, 2025)
Aim/Purpose: This study aims to assess the effectiveness of a tessellation-based instructional program supported by digital technologies for enhancing geometric learning in primary school pupils. Background: Digital education offers various benefits, including increased motivation and engagement, and has been shown to be effective in teaching geometry. Although tessellation activities have been shown to effectively support geometry learning at both secondary and primary school levels, in the current literature, their implementation in digital environments has been explored exclusively in secondary education. Methodology: A quasi-experimental research design was used, using 3D printers and GeoGebra software with an experimental group and a control group, including pre-tests and post-tests. The students were in Grade 4. The instructional activities were designed according to recent recommendations in geometry education, using real-life contexts, drawing, prediction and imagining shapes, and technological tools. Contribution: This paper makes two contributions to the field of primary geometry education and educational technology. First, it extends research on the effectiveness of tessellation activities in digital environments for learning geometry from secondary to primary school. Second, it provides new empirical evidence for the effectiveness of digital teaching in enhancing geometric learning outcomes at the primary level. Specifically, the study demonstrates how technological tools like 3D printers and GeoGebra software can be used effectively in primary education, positively impacting geometry learning and promoting high levels of student engagement. Findings: The results indicated that the experimental group showed significant improvements in post-test scores compared to the pre-test, while the control group did not. This supports the hypothesis that a tessellation-based program, implemented digitally, can enhance geometric learning in primary students. Additionally, a questionnaire revealed high satisfaction with the activities, particularly with the use of a 3D printer and GeoGebra software, suggesting that these tools increased student engagement. Recommendations for Practitioners: Primary school teachers should consider integrating digital tessellation activities into their geometry curriculum. Exploiting digital technologies like GeoGebra software can enhance students’ understanding of geometric concepts and increase engagement; moreover, 3D printing can provide tangible outcomes, reinforcing learning through hands-on experiences. Therefore, professional development in these technologies may be necessary. Recommendation for Researchers: Researchers could aim to isolate the specific effects of educational technologies, particularly 3D printers and GeoGebra software, on geometric learning outcomes. A design with multiple experimental groups would be beneficial: one with tessellation activities using technologies, one with tessellation activities without technologies, one with different activities aimed at achieving the same geometric learning outcomes, and a control group engaged in activities targeting different geometric learning outcomes. Impact on Society: The findings of this study could have broad implications for primary education and educational technology. They suggest a potential shift in how geometry is taught at the primary level, emphasizing the integration of digital tools and manipulative approaches like tessellation. If teacher training organizations begin to incorporate this program into their curriculum, many educators might adopt it, potentially fostering a better understanding of a fundamental subject like geometry and improving digital literacy in future generations. Future Research: While digital tessellation activities have been explored in secondary schools, their integration into primary education remains under-researched, highlighting the need for more studies examining their potential to enhance younger students’ geometric understanding through digital tools. Additionally, longitudinal studies could explore the long-term impact of digital tessellation activities on students’ geometric understanding and spatial skills. Future research could also investigate the transferability of skills acquired through these activities to other areas of mathematics. Comparative studies across different age groups and educational levels could provide insights into the optimal timing for introducing such interventions. Finally, exploring the potential of augmented or virtual reality in tessellation-based geometry learning could open new avenues for research in educational technology and mathematics education.